Relieving: reinterpreting the mall, the park and the public space in Sandton - Batev, Minki Magdalena (My University, 2019)
Stress is a reality of life. It can be good and bad and it can be constructive and the destructive. The destructive nature of stress can have a negative impact on a persons physical and mental health. Unfortunately, some stress is unavoidable, therefore a need to manage and alleviate stress is important. There is a general relationship between the built environment and stress. Looking at Sandton, the corporate centre of Johannesburg, it is understood why people experience professional, work pressure. The physical conditions of Sandton potentially further contribute to making Sandton a stressful environment. Sandton City, the mall situated in between Sandton’s corporate buildings, is in prime location with a under-utilised, empty flat roof. Herein lies an opportunity for a spatial intervention where people are able to alleviate constant streams of stress and in addition to improve the physical environment of Sandton to be more restorative and foster well-being in oder to enhance people’s ability to function effectively. This project is proposing that the roof of Sandton City is transformed into a public park. This responds to the need for more natural landscaping and to the need for public space in Sandton. The park will integrate into the mall at the main ‘social’ cores (the Checkers court, the Food court and Woolworths court). Most importantly, the park’s programming will address the issue of stress in the corporate environment by providing a variety of spaces and places for people to relax. This includes a exercise zone, a food zone and an urban escape zone which has a spa and short-stay rentable rooms.
For the fulfillment for Masters of Architecture (Professional) at the University of the Witwatersrand, Johannesburg, South Africa 2019
Keywords: Public spaces--Social aspects; Urbanization--South Africa; Public architecture